KATA SAPAAN KEKERABATAN BAHASA MELAYU RIAU DI DESA SAWAH KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI RIAU - Lidya Indah Sari; Sumiharti Sumiharti (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research aims to describe the kinship greetings in Desa Sawah Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi Riau. The study used the qualitative descriptive method. This research data is in the form of oral speeches of kinship greeting in Desa Sawah Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi Riau. Six informants become sources through the data collection technique by using the wind direction method. The results of this study are in the form of a description of the society’s kinship greeting in Desa Sawah Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi Riau. The analysis found that word kinship in marriage such as Tentuo (Uncle) and Ondek Esu (Aunt). Furthermore, the word kinship greeting is based on Tak Antan (Ancestor) and Tuan (Big Brother). There are 25 words of marital kinship, while there are 16 words of the kinship of greetings. Thus the whole greetings found in the data is 41 expressions. Keywords: Kinship Greetings, Riau Malay language